Does Advertising Productivity Affect Organizational Performance? Impact of Market Conditions. (6th September 2020) - Rahman, Mahabubur; Rodríguez‐Serrano, M. Ángeles; Hughes, Mathew
Abstract: Advertising is crucial in influencing customers' perceptions and purchase intentions, and numerous studies have investigated whether advertising expenditure has any significant impact on financial performance. A thorough understanding remains elusive: while several studies document a positive impact, others report that advertising has either a negative or a statistically insignificant effect. Three flaws among existing studies are responsible for this problem: bundling advertising with other forms of marketing, the inadequacy of expenditure as a measure and a failure to consider contingencies. Deviating from earlier studies, we examine the effect of advertising productivity on firm performance rather than the impact of the absolute amount of advertising expenditure . Moreover, adopting a contingency approach, we evaluate how market conditions of market dynamism, market complexity and market munificence moderate the relationship between advertising productivity and organizational performance. Drawing a multi‐industry sample from the USA, this study demonstrates that advertising productivity has a positive impact on capital market‐based performance measures, conditional on market conditions. We reveal new insights into when, why and to what extent advertising contributes (or not) to organizations' financial performance.